POTENTIAL OF BLACK TEA TO REDUCE FORMALDEHYDE LEVELS IN FRESH TUNA FISH (Auxis thazard) DURING IMMERSION TIME - Wahyu Vera Wardani (Jurnal Gizi dan Pangan Soedirman, 2020)
Saponin in black tea is predicted having potential to reduce formaldehyde level in preserved fresh tuna (Auxis thazard) using formaldehyde. This research used experimental design, post-test only control group. Variables examined were formaldehyde level, organoleptic values (eye appearance, gill appearance, color, smell, and texture), and soluble protein level. Formaldehyde level was analyzed using Nash reagent by spectrophotometric method. Organoleptic value was conducted using questionnaire by 16 panelists. Soluble protein level was analyzed using Lowry reagent by spectrophotometry. Result showed significant difference between formaldehyde level in control and treatment gorup, but did not significantly difference between formaldehyde level that was immersed in water and black tea solution. Soluble protein level showed no significant difference between samples. There were significant differences in appearance and eye color, while there were no differences in gill appearance, smell and texture. The best treatment was samples immersed in black tea 1,5% for 90 minutes with average levels of formaldehyde 55,76 ug/g, soluble protein content of 0,042 mg/g, eyes appearance 1,59 (slightly white orange), the appearance of gills 2,41 (less crimson), 2,78 body color appearance (slightly orange white), the smell of 2,63 (pungent), the texture of 1,69 (slightly soft). Keyword : black tea, formaldehyde, saponin